Mass media law - Pember, Don R., 1939-; Calvert, Clay (Law professor) (New York, NY : McGraw-Hill Education, 1977)
"In its 19th edition, Mass Media Law offers an updated look at the ever-changing landscape of media law. It continues to provide undergraduates with the foundation they need to understand the field, going back to the adoption of the First Amendment, and quickly brings them up to speed with the most current issues. In their popular conversational style, Don Pember and Clay Calvert introduce students to the newest threats to journalism and the role technology plays in the field of mass media law. The attention this program provides to both historical and contemporary issues gives students the background they need to fully understand the controversies surrounding speech and press across media"--
"Since the last edition of the textbook, the U.S. Supreme Court handed down important rulings in more than a half-dozen, high-profile cases affecting freedom of speech, access to information, and jury bias. Those rulings from 2010 and 2011, all of which are addressed in this new edition, include - United States v. Stevens, in which the Court declared as unconstitutionally overbroad a federal statute that criminalized the commercial creation, sale or possession of certain depictions of animal cruelty, and, in particular, so-called "crush videos" (see Chapters 1 and 2). In issuing its ruling, the Court refused to carve out a new category of unprotected speech for images of animal cruelty - Brown v. Entertainment Merchants Association, in which the Court declared unconstitutional a California statute limiting minors' access to purchasing and renting violent video games (see Chapter 2). The decision hopefully will put an end to similar state and local legislation that seems to be adopted every time a school shooting occurs and legislators blame the violent media content"--
The American Legal System -- The First Amendment: The Meaning of Freedom -- The First Amendment: Contemporary Problems -- Libel: Establishing a Case -- Libel: Proof of Fault -- Libel: Defenses and Damages -- Invasion of Privacy: Appropriation and Intrusion -- Invasion of Privacy: Publication of Private Information and False Light -- Gathering Information: Records and Meetings -- Protection of News Sources/Contempt Power -- Free Press-Fair Trial: Trial-Level Remedies and Restrictive Orders -- Free Press-Fair Trial: Closed Judicial Proceedings -- Regulation of Obscene and Other Erotic Material -- Copyright -- Regulation of Advertising -- Telecommunications Regulation.
Includes bibliographical references and index.
Keywords: Mass media -- Law and legislation -- United States; Press law -- United States; Mass media -- Law and legislation; Press law; United States